Search for CP violation in D0→π−π+π0 decays with the energy test - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (Physics letters, 2015)
A search for time-integrated CP violation in the Cabibbo-suppressed decay D0→π−π+π0 is performed using for the first time an unbinned model-independent technique known as the energy test. Using proton-proton collision data, corresponding to an integrated luminosity of 2.0 fb−1 collected by the LHCb detector at a centre-of-mass energy of s=8 TeV, the world's best sensitivity to CP violation in this decay is obtained. The data are found to be consistent with the hypothesis of CP symmetry with a p-value of (2.6±0.5)%.
Available online 25 November 2014
Im Titel sind "+", "-" und "0" hochgestellt
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, M. Fontana, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelezov [und 672 weitere]
Gesehen am 07.04.2021